Dysthyroid Orbitopathy Presenting with Gaze-Evoked Amaurosis: Case Report and Review of the Literature. (2nd November 2015) - Orlans, Harry O.; Bremner, Fion D.
Abstract: Background : Gaze-evoked amaurosis (GEA) describes visual loss associated with eccentric gaze that recovers when the eye is returned to primary position. Here we describe an unusual case of bilateral GEA as the presenting feature of dysthyroid orbitopathy. This is only the third such case to be reported in the literature and the first to feature bilateral GEA in all positions of gaze without accompanying proptosis or ophthalmoplegia. Case Presentation : A 50-year-old man who had recently commenced treatment for thyrotoxicosis presented with a 3-week history of typical GEA in both eyes in all positions of gaze. He subsequently developed a bilateral compressive optic neuropathy which was only partially responsive to high dose steroid therapy. Conclusion : Although an uncommon presenting feature of dysthyroid orbitopathy, GEA is an ominous symptom that may precede sight-threatening optic nerve compromise. When present, early immunosuppressive and/or decompressive treatment should be considered.